2017
DOI: 10.3389/fpls.2017.01793
|View full text |Cite
|
Sign up to set email alerts
|

Hexanoic Acid Treatment Prevents Systemic MNSV Movement in Cucumis melo Plants by Priming Callose Deposition Correlating SA and OPDA Accumulation

Abstract: Unlike fungal and bacterial diseases, no direct method is available to control viral diseases. The use of resistance-inducing compounds can be an alternative strategy for plant viruses. Here we studied the basal response of melon to Melon necrotic spot virus (MNSV) and demonstrated the efficacy of hexanoic acid (Hx) priming, which prevents the virus from systemically spreading. We analysed callose deposition and the hormonal profile and gene expression at the whole plant level. This allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 68 publications
2
21
0
Order By: Relevance
“…These results demonstrate that fungal growth arrest after chitosan treatment is not directly mediated by the toxicity effect of the chemical, as the infected leaves were formed after treatment and therefore were not sprayed with the elicitor. Moreover, these results demonstrate similar priming mechanisms after chitosan treatment to other elicitors, including Hx, which has been linked with priming of callose and JA against B. cinerea (Fernández-Crespo et al, 2017, Wang et al, 2014). Interestingly, however, despite many reported antagonistic and other crosstalk interactions between plant hormones (Robert-Seilaniantz et al, 2011), the concentrations of other plant hormones, SA and ABA, were not affected.…”
Section: Discussionsupporting
confidence: 69%
“…These results demonstrate that fungal growth arrest after chitosan treatment is not directly mediated by the toxicity effect of the chemical, as the infected leaves were formed after treatment and therefore were not sprayed with the elicitor. Moreover, these results demonstrate similar priming mechanisms after chitosan treatment to other elicitors, including Hx, which has been linked with priming of callose and JA against B. cinerea (Fernández-Crespo et al, 2017, Wang et al, 2014). Interestingly, however, despite many reported antagonistic and other crosstalk interactions between plant hormones (Robert-Seilaniantz et al, 2011), the concentrations of other plant hormones, SA and ABA, were not affected.…”
Section: Discussionsupporting
confidence: 69%
“…On the other hand, studies on the use of chemicals to control viral diseases are scarce (Fernández‐Crespo et al . ). Different compounds have been used to prevent or reduce infection by different pathogens including plant viruses.…”
Section: Discussionmentioning
confidence: 97%
“…In a more recent work, it has been reported that hexanoic acid prevents the spread of MNSV ( Melon necrotic spot virus ) in melon plants (Fernández‐Crespo et al . ). This response was parallel to an increase in callose deposition and ferulic acid, as well as to a decrease in H 2 O 2 accumulation in the cotyledons.…”
Section: Discussionmentioning
confidence: 97%
“…The callose of rice leaves was stained on the infiltration site with aniline blue and then the samples were cytologically observed by using UV fluorescence microscopy. The leaves of rice were infiltrated with 2.0 µM of HrpE, while RFP protein served as control in this study, and the callose staining for leaves of each treatment was observed by using UV fluorescence microscopy 24 hpi as reported [30]. Image J software was used to estimate the callose intensity from digital photographs by the number of blue pixels as compared to the total number of pixels covering the leaves.…”
Section: Methodsmentioning
confidence: 99%